2017
DOI: 10.3390/f8100373
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Carbon, Nitrogen and Phosphorus Concentrations and C:N:P Stoichiometry in the Leaves of Differently Aged Larix principis-rupprechtii Mayr. Plantations

Abstract: Abstract:The concentrations and stoichiometry of certain elements (carbon, nitrogen and phosphorus) are critical to the maintenance of plant functional and environmental adaptation during plant growth. We explore how the concentrations of C, N and P and the ratios of C:N, C:P, and N:P in the leaves of differently aged Larix principis-rupprechtii Mayr. plantations changed with growing season and stand age from 2012 to 2015 in the Qinling Mountains, China. The results showed that the element concentration and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
2
26
2
Order By: Relevance
“…In addition, the C:P and N:P ratios of the leaves were higher than the Chinese and global averages, while C:N was lower than the global average (Table 4). These differences may be related to different vegetation types, climatic features, and sampling periods [33][34][35]. Notably, previous studies have found that the P content and C:N ratio of the R. pseudoacacia leaves in the Loess Plateau were significantly higher than the Chinese and global averages [27,36], which is inconsistent with our results.…”
Section: Seasonal Variations Of the C N And P Contents And Ratios Ocontrasting
confidence: 99%
“…In addition, the C:P and N:P ratios of the leaves were higher than the Chinese and global averages, while C:N was lower than the global average (Table 4). These differences may be related to different vegetation types, climatic features, and sampling periods [33][34][35]. Notably, previous studies have found that the P content and C:N ratio of the R. pseudoacacia leaves in the Loess Plateau were significantly higher than the Chinese and global averages [27,36], which is inconsistent with our results.…”
Section: Seasonal Variations Of the C N And P Contents And Ratios Ocontrasting
confidence: 99%
“…Our findings indicate that the soil C, N, and P concentration ratios respond to thinning, although the range of change is unpredictable according to other studies [28,48]. Specifically, the STC:STN, STC:STP, and STN:STP ratios were significantly influenced by MIT, and light and high intensity thinning treatments significantly affected the STC:STP ratio.…”
Section: Variation Of Soil Properties and Stoichiometry Following Thisupporting
confidence: 63%
“…Our stringent control of incident light for each plant regardless of size removed this ambiguity from our methods, leaving plant height as the only known factor controlling the quantified variations in leaf nutrient levels. Second, many of the papers that emerge in literature searches compared stand age, not plant age per se [33,55,56,57,58]. The results in these studies are complicated by the maturing plant–soil feedback changes that co-occur with the increase in plant size.…”
Section: Discussionmentioning
confidence: 99%